Identification of ability to form biofilm in Candida parapsilosis and Staphylococcus epidermidis by Raman spectroscopy - Rebrošová, Katarína; Šiler, Martin; Samek, Ota; Růžička, Filip; Bernatová, Silvie; Ježek, Jan; Zemánek, Pavel; Holá, Veronika (Future microbiology, 2019)
Aim: Finding rapid, reliable diagnostic methods is a big challenge in clinical microbiology. Raman spectroscopy is an optical method used for multiple applications in scientific fields including microbiology. This work reports its potential in identifying biofilm positive strains of Candida parapsilosis and Staphylococcus epidermidis. Materials & methods: We tested 54 S. epidermidis strains (23 biofilm positive, 31 negative) and 51 C. parapsilosis strains (27 biofilm positive, 24 negative) from colonies on Mueller-Hinton agar plates, using Raman spectroscopy. Results: The accuracy was 98.9% for C. parapsilosis and 96.1% for S. epidermidis. Conclusion: The method showed great potential for identifying biofilm positive bacterial and yeast strains. We suggest that Raman spectroscopy might become a useful aid in clinical diagnostics.
Keywords: Staphylococcus epidermidis; biofilm; Candida parapsilosis; Diagnostic Tests, Routine; rapid diagnostics; lidé; biofilmy; Raman spectroscopy; Biofilms; diagnostické testy rutinní; Spectrum Analysis, Raman; Ramanova spektroskopie; Humans